Pengaruh Variasi Massa Raw Material, Jenis Material dan Kedalaman Pemakanan Terhadap Respon Steady State Error pada Motor Penggerak Slider Mesin Lathe Mini - Wahyu Stiyo Budi; Ahmad Anas Arifin; Desmas Arifianto Patriawan (Institut Teknologi Adhi Tama Surabaya, 2022)
As time goes by, the world's technology is growing rapidly, as evidenced by the existence of manufacturers in the manufacturing sector such as lathe machines. In the lathe industry, it is very necessary to make it easier to work on the manufacture of custom components such as nuts, bolts and others, therefore this research was carried out using the incremental zero point measurement method using a caliper and testing was carried out based on variations including variations in the mass of raw materials, variations depth of eating, variations in material types. Besides that, this study modifies the mini manual lathe machine into an Arduino-based mini lathe machine (Semi-automatic) so that the operation of the machine can minimize the level of loss in terms of time and cost. This research focuses on testing the performance of the cylindrical motor with the method of calculating settling time, steady state error and variations in the type of working material in order to improve accuracy, precision and time efficiency in processing.Keywords: Steady state error, lathe, spindle